Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.3390/ma11010156
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication, Structural Characterization and Uniaxial Tensile Properties of Novel Sintered Multi-Layer Wire Mesh Porous Plates

Abstract: There is an increasing interest in developing porous metals or metallic foams for functional and structural applications. The study of the physical and mechanical properties of porous metals is very important and helpful for their application. In this paper, a novel sintered multilayer wire mesh porous plate material (WMPPs) with a thickness of 0.5 mm–3 mm and a porosity of 10–35% was prepared by winding, pressing, rolling, and subsequently vacuum sintering them. The pore size and total size distribution in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 21 publications
0
18
2
Order By: Relevance
“…In the first step, the 304 stainless steel wire mesh was cut into strips. The microstructure of the stainless steel wire mesh with 80 μm wire diameter is shown in our previous work . The warp wires and weft wires were crisscrossed to form inerratic square pores.…”
Section: Methodsmentioning
confidence: 92%
“…In the first step, the 304 stainless steel wire mesh was cut into strips. The microstructure of the stainless steel wire mesh with 80 μm wire diameter is shown in our previous work . The warp wires and weft wires were crisscrossed to form inerratic square pores.…”
Section: Methodsmentioning
confidence: 92%
“…The pressing of wire semiproducts does not usually provide permanent fixing of wire turns at their ends, particularly when elastic or rigid wire is used ( Figure 5,a). In addition, the lack of sintering operation, traditionally performed in metallurgic processes involving powder and fibrous products, gives no possibility to render extra strength to the product (Balshin, 1972;Liu et al, 2008;Duan et al, 2018). Therefore, the problem how to prevent damage to the packing ends, specifically unwinding of wire turns, can be solved by strengthening the turns at both ends, for example by using connecting tips.…”
Section: Fixing Of the Packing Endsmentioning
confidence: 99%
“…Porosity and pore structure also have great influence on the mechanical properties [ 5 ]; the tensile properties of metal porous materials are one of the indicators that cannot be ignored. Research on the tensile properties of porous materials has shown that the higher the porosity is, the lower will be the strength and stiffness [ 6 , 7 ]. The sintering temperature has an obvious effect on the tensile strength of the composite porous materials [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%